Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1080/02713680590907256
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Orthokeratology Research in Children (LORIC) in Hong Kong: A Pilot Study on Refractive Changes and Myopic Control

Abstract: Cómo citar este artículo: Ortega Pacific EJ, Rodríguez Rodríguez A. Control de la miopía con ortoqueratología. Cienc Tecnol Salud Vis Ocul. 2017;15(1):69-78. doi: http://dx.doi.org/10.19052/sv.3905 RESUMEN La ortoqueratología ha tenido un gran auge en los últimos años, debido a la aparición de nuevos materiales y diseños que han facilitado su aplicación; por esta razón, se planteó desarrollar una revisión que permitiera analizarla desde aquellos pacientes en quienes se ha usado. Objetivos: mostrar la eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
384
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(443 citation statements)
references
References 23 publications
29
384
0
9
Order By: Relevance
“…While these data provide a reference point, they do not provide normative data on axial length increase during childhood. This is due to numerous variables that may contribute to refractive and axial length changes including age of myopia onset [27,31], ethnicity [31][32][33][34][35][36], hours of near work [37], hours of time spent outdoors [38], mode of refractive correction [20,24,39] and parental history of myopia [40]. …”
Section: Axial Length Changes With Other Modes Of Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these data provide a reference point, they do not provide normative data on axial length increase during childhood. This is due to numerous variables that may contribute to refractive and axial length changes including age of myopia onset [27,31], ethnicity [31][32][33][34][35][36], hours of near work [37], hours of time spent outdoors [38], mode of refractive correction [20,24,39] and parental history of myopia [40]. …”
Section: Axial Length Changes With Other Modes Of Correctionmentioning
confidence: 99%
“…Ortho-K is the application of specially-designed, reverse-geometry; rigid-gas-permeable contact lenses worn only while sleeping to temporarily reshape the cornea, such that refractive error is corrected without the need to wear any correction during waking hours. To date, numerous clinical studies have reported a beneficial effect of Ortho-K on slowing or stopping myopic progression [20][21][22][23][24][25]. Ortho-K requires adherence to prescribed wear time, and children in one retrospective study were shown to be very adherent to the prescribed Ortho-K wearing schedule [26].…”
Section: Introductionmentioning
confidence: 99%
“…12 Although a retrospective study 13 and a case report 14 on the subject were previously published, only two prospective studies have assessed the effect of orthokeratology contact lens wear on myopia progression in children. 15,16 Over a two-year period, Cho et al 15 monitored the increase in axial length in 35 Hong-Kong Chinese children aged 7 to 12 who were fitted with orthokeratology lenses, and compared the rate of change of axial length with that observed in a historical control group made up of 35 children wearing single-vision spectacles. Both groups were matched for age, gender and baseline spherical equivalent refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Walline et al 16 study was unable to recruit a prospective control group. Since Cho et al 15 and Walline et al 16 employed historical prospective control groups, subjects were not randomized into one modality of visual correction vs. another. Additionally, these two previous studies measured axial-length growth using A-scan ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2005) and Walline et al (2009) were first to report 47% and 55% less axial elongation respectively when compared to historical controls over 2 years of OK lens wear. Swarbrick et al (2015) demonstrated a halt in myopic progression of OK treated eyes when compared to contralateral RGP-wearing eyes over two six-month periods in a crossover study.…”
Section: Orthokeratology: Effect On Myopia Progressionmentioning
confidence: 99%